Exploring pregnant women’s expectations, perceptions, and satisfaction with antenatal care services in Lumbini province, Nepal: a cross-sectional study - Ruchal, Rajendra; Singh, Sumer; Pant, Pradip Raj (International Journal Of Community Medicine And Public Health, 2024)
Background: Antenatal care (ANC) plays a crucial role in ensuring the health and well-being of pregnant women by providing regular checkups to identify potential complications and deliver important guidance on pregnancy and childbirth. While the expectations surrounding ANC services are shaped by user’s individual needs and preferences, the quality of care experienced is largely determined by the service providers. The level of service quality significantly influences the utilization of ANC service, as women are more likely to use services that satisfied their expectations. This study aimed to assess the expectations, perceptions, and satisfaction levels of pregnant women concerning the ANC services offered by health institutions in Lumbini Province. Methods: An institution-based cross-sectional analytical study was carried out involving 2,986 pregnant women, selected through multistage cluster sampling. Quantitative analysis was carried out to calculate the perception, expectation, and satisfaction score. The SERVQUAL tool was utilized to measure expectation, perception and service quality gap. Results: The study involved 2,986 pregnant women, the majority of whom (76.7%) were aged 20-30 years, 38.5% were Janajati, most of them (32.5%) had a secondary level of education, and 78.8% were housewives. The expectation score was higher than the perception. Overall, only 67% of pregnant women were satisfied with the services. Conclusions: Significant disparities exist between the expectations and actual perceptions of ANC users, indicating a lower level of satisfaction among mothers with the ANC services. The study concluded that decreased satisfaction with the service is likely to reduce the trend of service utilization.